Pemertahanan Eksistensi Diri dalam Drama Delailah Tak Ingin Pulang dari Pesta: Kajian Psikologi Humanistik - Titik Maslikatin (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2013)
Delailah Tang Ingin Pulang dari Pesta is a drama that is able to read the events around him. Incessanttelevision that catapulted figure kewaria-warian make genuine transvestite want to demand their rights.Delailah singer and dancer whose members who wanted to maintain the "nature" and want to berecognized as human beings with a variety of mental suffering. Be the preferred method ofpsychological analysis to uncover conflicts incest figure in maintaining the existence itself. Melalauistudy of humanistic psychology can be interpreted that Delailah maintain his existence withachievements not sell "face" or selling yourself. The existence of one supreme self Delaila member tobecome a famous artist is achieved due to the hard work and creativity.